AKTIVITAS ANTIOKSIDAN EKSTRAK DAN FRAKSI EKSTRAK BIJI ATUNG (Parinarium glaberrimum Hassk.) [Antioxidant Activities of Parinarium glaberrimum Hassk Extracts and their Fractions] - Dewi Sarastani; Soewarno T. Soekarto; Tien R. Muchtadi; Dedi Fardiaz; Anton Apriyantono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
The seed of Parinarium glaberrimum Hassk was extracted with non polar solvent (hexane) and or polar solvent (ethanol). Antioxidative activity of extracts was measured by rates of carotene bleaching in the coupled oxidation of linoleic acid and b-carotene. Ethanolic-Hexanoic Extract (EHE) of the seed was found to possess the highest antioxidative activity. Furthermore, EHE was fractionated by silica column chromatography and eight major fractions were isolated according to UV absorption. Antioxidative activity of these fractions was evaluated in a b-carotene-linoleate system. Fractions III , I , and II showed the major activity, but fractions I and II have the best value of relative capacity, so they were chosen for further identification.